Being a relative of an addict: al-anon self-help groups as a family-based practice model in the search for psychosocial support - Yılmaz, Yelda; Sarıtepe, Doğukan Furkan; Acar, Burak (Journal of Dependence, 2025)
Objective: The present study seeks to elucidate the psychosocial challenges encountered by the relatives of individuals with alcohol addiction and to critically assess the contributions provided by Al-Anon groups.Method: Utilizing a qualitative research design, in-depth, semi-structured interviews were conducted with 13 individuals who regularly participated in Al-Anon meetings in Istanbul and who were relatives of persons with alcohol dependency. The data were analyzed through descriptive content analysis.Results: Participants’ narratives were organized around four principal themes: (1) the initial confrontation with alcohol addiction, (2) the psychosocial challenges of being a relative of an addicted individual, (3) the process of engagement with Al-Anon, and (4) the perceived contributions of Al-Anon groups. Participants indicated that through Al-Anon, they came to recognize that they were not alone, ceased patterns of self-blame, developed the capacity to establish personal boundaries, and enhanced their ability to assert themselves by saying “no.”Conclusion: The findings underscore that Al-Anon self-help groups serve as a critical psychosocial resource for the relatives of individuals with alcohol addiction. Addressing addiction effectively necessitates the support of not only the affected individual but also the entire family system. In this regard, it is imperative to promote and expand initiatives that enhance the visibility, empowerment, and help-seeking behaviors of relatives of addicted individuals.
Keywords: Self-help; alcohol; relative of an addicted individual; addiction